Procedural Requirements for the Expert’s Opinion in Criminal Proceedings - Piliukov, Yurii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article deals with the procedural features of the formation, verification and evaluation of the expert’s conclusion. Proposed separate additions to the Criminal Procedure Code of Ukraine on the order of involving an expert by the parties to the criminal proceedings.